Microsatellite instability as a predictive factor for immunotherapy in malignant melanoma - Kubecek, Ondrej; Trojanova, Petronela; Molnarova, Veronika; Kopecky, Jindrich (Medical hypotheses, 2016)
Immunotherapy has attracted attention as a novel treatment modality for malignant melanoma. Although the use of immunotherapy in metastatic melanoma has shown promising results, there remains a lack of predictive biomarkers indicating treatment benefit from immunotherapy. There is growing evidence suggesting that microsatellite instability (MSI) as a product of DNA mismatch repair deficiency, may be one of possible predictive markers in malignant melanoma. It has been proposed that the immunogenicity of some tumors might be determined by mutational heterogeneity and could be the key to the success of immune therapies. This is also supported by the fact that tumors with the highest amount of somatic mutations, such as malignant melanoma have showed positive results with immune checkpoint inhibitors. There are promising data regarding the association between MSI status and immunogenicity from studies with colorectal cancer, where MSI is linked to improved prognosis compared to microsatellite stable cancers. MSI in colon cancer is linked to a significant increase of immunocompetent cells responsible for the antitumor activity - CD3(+), CD8(+), CD45RO(+), and T-bet(+) lymphocytes and decrease of inhibition factors such as Foxp3, IL-6, IL-17, and TGF-β. On the other hand, taking into account the progression-dependent accumulation of somatic mutations in MSI tumors and consequent high levels of neo-antigens, the possible drug resistance of MSI tumors to traditional treatment, and the presence of inhibition checkpoints within the MSI tumors, there is a solid rationale for the use of novel therapeutic strategies such as immunotherapy in MSI melanomas. We presume that the MSI phenotype in malignant melanoma might be helpful to identify patients, who would be more likely to profit from immunotherapy than from conventional therapy.
Keywords: mutace; oprava DNA; teoretické modely; mikrosatelitní nestabilita; Antigens, Neoplasm; Immunotherapy; lidé; Mutation; DNA Repair; Microsatellite Instability; T-lymfocyty; prognóza; nádory kůže; melanom; imunoterapie; Skin Neoplasms; Microsatellite Repeats; Prognosis; T-Lymphocytes; Models, Theoretical; mikrosatelitní repetice; antigeny nádorové; Melanoma; Humans